Active Involvement of End Users When Developing Web-Based Mental Health Interventions - de Beurs, Derek; van Bruinessen, Inge; Noordman, Janneke; Friele, Roland; van Dulmen, Sandra (Frontiers in Psychiatry, 2017)
Background Although many web-based mental health interventions are being released, the actual uptake by end-users is limited. The marginal level of engagement of end-users when developing these interventions is recognized as an important cause for uptake problems. In this paper we offer our perceptive on how to improve user engagement. By doing so we aim to stimulate a discourse on user involvement within the field of online mental health interventions. Methods We shortly describe three different methods (the expert driven method, intervention mapping, and scrum) that were currently used to develop web-based health interventions. We will focus to what extent the end-user was involved in the developmental phase, and what the additional challenges were. In the final paragraph, lessons learned are summarized, and recommendations provided. Results Every method seems to have its trade-off: if end-users are highly involved, availability of end-users and means become problematic. If end users are less actively involved, the product may be less appropriate for the end-user. Other challenges to consider are the funding of the more active role of technological companies, and the time it takes to process the results of shorter development cycles. Conclusions Thinking about user-centred design and carefully planning the involvement of end-users should become standard in the field of web-based (mental) health. When deciding on the level of user-involvement, one should balance the need for input from users with the availability of resources such as time and funding.